The pattern of genetic diversity of different breeds of pigs based on microsatellite analysis - V. R. Kharzinova; N. A. Zinovieva (Вавиловский журнал генетики и селекции)
One of the main tasks of genetics and animal breeding is the assessment of genetic diversity and the study of genetic relationships between different breeds and populations using molecular genetic analysis methods. We analysed the polymorphism of microsatellites and the information on the state of genetic diversity and the population structure of local breeds in Russia: the Kemerovo, the Berkshire, the Liven, the Mangalitsa, and the Civilian; in the Republic of Belarus: the Large White and the Black-and-White; and in Ukraine: the White Steppe, as well as commercial breeds of imported origin of domestic reproduction: the Large White, the Landrace, and the Duroc. The materials used for this study were the tissue and DNA samples extracted from 1,194 pigs and DNA of the UNU “Genetic material bank of domestic and wild animal species and birds” of the L.K. Ernst Federal Research Center for Animal Husbandry. Polymorphisms of 10 microsatellites (S0155, S0355, S0386, SW24, SO005, SW72, SW951, S0101, SW240, and SW857) were determined according to the previously developed technique using DNA analyser ABI3130xl. To estimate the allele pool of each population, the average number of alleles (NA), the effective number of alleles (NE ) based on the locus, the rarified allelic richness (AR), the observed (HO ) and expected (HE ) heterozygosity, and the fixation index (FIS) were calculated. The degree of genetic differentiation of the breeds was assessed based on the pairwise values of FST and D. The analysis of the allelic and genetic diversity parameters of the local breeds showed that the maximum and minimum levels of polymorphism were observed in pigs of the Ukrainian White Steppe breed (NA = 6.500, NE = 3.709, and AR = 6.020) and in pigs of the Duroc breed (NA = 4.875, NE = 2.119, and AR = 3.821), respectively. The highest level of genetic diversity was found in the Large White breed of the Republic of Belarus (HO = 0.707 and NE = 0.702). The minimum level of genetic diversity was found in pigs of the imported breeds – the Landrace (HO = 0.459, HE = 0.400) and the Duroc (HO = 0.480, HE = 0.469) – indicating a high selection pressure in these breeds. Based on the results of phylogenetic analysis, the genetic origin of Large White pigs, the breeds, from which the Berkshire pigs originated, and the genetic detachment of the Landrace from the Mangalitsa breeds were revealed. The cluster analysis showed a genetic consolidation of the Black-and-White, the Berkshire, and the Mangalitsa pigs. Additionally, the imported breeds with clustering depending on the origin were characterised by a genetic structure different from that of the other breeds. The information obtained from these studies can serve as a guide for the management and breeding strategies of the pig breeds studied, to allow their better use and conservation.